Autoclaving-treated germinated brown rice relieves hyperlipidemia by modulating gut microbiota in humans - Ren, Chuanying; Hong, Bin; Zhang, Shan; Yuan, Di; Feng, Junran; Shan, Shan; Zhang, Jingyi; Guan, Lijun; Zhu, Ling; Lu, Shuwen (Frontiers in Nutrition, 2024)
Germinated brown rice is a functional food with a promising potential for alleviating metabolic diseases. This study aimed to explore the hypolipidemic effects of autoclaving-treated germinated brown rice (AGBR) and the underlying mechanisms involving gut microbiota. In patients with hyperlipidemia, dietary intervention with AGBR or polished rice (PR) was implemented for 3 months, and blood lipids and gut microbiota were analyzed. The results showed that AGBR relieves hyperlipidemia in patients, as evidenced by reduced levels of triglycerides, total cholesterol, low-density lipoprotein cholesterol, and apolipoprotein-B, and elevated levels of high-density lipoprotein cholesterol and apolipoprotein-A1. In terms of nutrition, AGBR had significantly higher concentrations of free amino acids (10/16 species), γ-aminobutyric acid, resistant starch, soluble dietary fiber, and flavonoids (11/13 species) than PR. In addition, higher microbial abundance, diversity, and uniformity were observed in the AGBR group than in the PR group. At the phylum level, AGBR reduced Firmicutes, Proteobacteria, Desulfobacterota, and Synergistota, and elevated Bacteroidota and Verrucomicrobiota. At the genus level, AGBR elevated Bacteroides, Faecalibacterium, Dialister, Prevotella, and Bifidobacterium, and reduced Escherichia-Shigella, Blautia, Romboutsia, and Turicibacter. In summary, AGBR contributes to the remission of hyperlipidemia by modulating the gut microbiota.